Postoperative radiotherapy in the treatment of endometrial cancer: Review of 158 patients - Allouche, Fadwa; Terrab, Fatima Zahra; Ghammad, Sanae; Ennouichi, Rajae; Alami, Zineb; Bouhafa, Touria; Hassouni, Khalid (Journal of Surgery and Medicine, 2019)
Aim: Endometrial cancer is the most common gynecological cancer in the West. It is the third cancer of women after that of the breast and intestine. It mainly concerns menopausal women. Our aim is to highlight, through a retrospective study and in light of literature data, the role of radiotherapy in the management of this cancer. Methods: This is a retrospective cohort study concerning patients’ records for endometrial in the radiotherapy department at university hospital center of FEZ for a period of 5 years from January 2012 to December 2016. Results: We collected 158 patients of mean age 64 years (36 to 92 years), all patients had a total hysterectomy with (76% of cases) or without (24% of cases) ganglion dissection. Type 1 was the most common histological type (96% of cases). The myometrial invasion was greater than 50% in 51% of cases, histological grade III in 36% of cases, and cervical invasion was observed in 16% of cases. Therapeutically, 18% of patients received exclusive external radiotherapy at a dose of 50 Gy in conventional fractionation and spreading, a TEN at a dose of 46 Gy followed by a brachytherapy dam in 58% of cases, and 24% of patients received brachytherapy alone. After an average follow-up of 25 months, 91% of the patients are in good locoregional control, 9% of the patients had distant metastases. Conclusion: Radiotherapy retains an important place in the therapeutic strategy of high endometrial cancers, or with unfavorable histological characters, and thus allows the reduction of locoregional recurrence rates.